STUDY ON THE NOVELS OF JHAMPALAHIRI AND CHITRA BANERJEE DIVAKARUNI - ARUNDHATEE (International Journal of Multidisciplinary Research and Studies, 2021)
The term "diaspora" refers to a group of dispersed individuals who share a cultural background but live in different parts of the world. It also refers to people of a certain ethnic group who have voluntarily or because of outside influences departed the country in which they were born. In contrast to the influential migration, which refers to the forcible banishment of people from their native land arising due to social, political, or economic reasons such as the indentured labor system or the partition of India and Pakistan, the intentional migration from a native land to an alien land includes migration for the purpose of education, employment opportunities, marriage, and other social reasons. Immigrants face a variety of challenges when they move to a country that is part of a diaspora, including a sense of dislocation, cultural friction, and identity ambiguity. Diaspora literature, also known as diasporic literature, is a literary genre that was established when immigrant authors began writing about the experiences of those living in diaspora. Indian Diasporic Literature has developed as a result of the creative contributions made by authors of Indian descent such as Bharati Mukharjee, Kiran Desai, Amitav Ghosh, V. S. Naipul, Salman Rushdie, Meena Alexander, Jhumpa Lahiri, and Chitra Banerjee Divakaruni, amongst others. This research will specifically focus on the topic of diaspora and will attempt to apply characteristics of diaspora to several works of fiction written by Jhumpa Lahiri and Chitra Banerjee Divakaruni.